Do baixo clero ao planalto: construção da imagem de Jair Bolsonaro na imprensa (1991-2018) - Silveira, André Carlos Zorzi Freire da (Universidade Federal de São Carlos, 2025)
This paper aims to analyze how Jair Bolsonaro built his public image based on his appearances in the press while he was a congressman. Bolsonaro was elected president of Brazil in 2018 after a 27-year career as a congressman, but without significant control of institutional political powers during his career in Congress. In this sense, we assume that the public visibility accumulated for the 2018 campaign comes from his communication strategies throughout his career as a deputy. Thus, we analyzed his appearances in the press (including newspapers O Estado de S. Paulo and Folha de S. Paulo) between 1991 and 2018, in order to scrutinize whether (a) there were significant differences in the topics for which Bolsonaro appeared in the press over time; (b) Bolsonaro used the strategy of addressing more the topics that gave him more visibility; and (c) Bolsonaro changed the content of his speech from the moment he expressed his intention to run for president. We also assume that public images are relevant in shaping electoral competition, but also an important source of political capital during terms in office. We conclude that both the topics on which Bolsonaro appeared in the press and the content of much of his discourse underwent significant changes throughout the period encompassing his terms in office, with indications that the politician sought to address issues that would give him greater visibility more frequently. Bolsonaro also had greater exposure in the media when he was involved in controversies and, in some cases, when there was repercussion from the deputy's appearances on TV, taking advantage, as a rational political actor, of the functioning mechanisms of the Brazilian written press to maintain his public image in the spotlight throughout his terms in office.
From the 'baixo clero' to the 'planalto': construction of Jair Bolsonaro's image in the press (1991-2018)
Keywords: Eleições; Jornalismo; Jair Bolsonaro; Trajetória; Imagem pública; Public Image; Elections; Journalism; Trajectory; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO